Nanofiber Cellulose‐Incorporated Nanomesh Graphene–Carbon Nanotube Buckypaper and Ionic Liquid‐Based Solid Polymer Electrolyte for Flexible Supercapacitors. Issue 5 (12th April 2019) - Choi, Yeon Jun; Jung, Dae Soo; Han, Jae Hee; Lee, Geon-Woo; Wang, Sung Eun; Kim, Young Hwan; Park, Byung Hoon; Suh, Dong Hack; Kim, Tae-Ho; Kim, Kwang-Bum
Abstract : Flexible all‐solid‐state supercapacitors are actively investigated for their potential applications in flexible and wearable electronic devices. The important challenge in this field is to achieve a long‐term cycling stability under repeated bending and high energy. Herein, the design and synthesis of the following are reported: 1) nanofiber cellulose (NFC)‐incorporated nanomesh graphene–carbon nanotube (CNT) hybrid buckypaper electrodes with an excellent flexibility and a high specific capacitance and 2) an ionic liquid‐based solid polymer electrolyte with an excellent mechanical flexibility to realize the aims. Herein, the NFC is used to increase the packing density of the buckypaper through the hydrophobic interaction with CNTs, thereby improving the mechanical flexibility. As for the solid polymer electrolyte, the crosslinked structure is induced to provide the pathways for ion conduction and mechanical integrity even at a high ionic liquid content by chemically attaching triethoxysilane end groups to poly(ethylene oxide)‐poly(propylene oxide)‐poly(ethylene oxide) triblock copolymer. The sandwich structure of 1) and 2) exhibits an excellent cycling stability over 5000 bending cycles and high areal energy density (247 μWh cm −2 ), which are superior to those previously reported in flexible supercapacitors. Abstract : In this article, nanofiber cellulose‐incorporated nanomesh graphene–carbon nanotube hybrid buckypaper electrodes with an excellent flexibility, a high specific capacitance, and an ionic liquid‐based solid polymer electrolyte with an excellent mechanical flexibility and a high ionic conductivity are synthesized for flexible all‐solid‐state supercapacitor applications.